Humanity refines art, Art reveals life.: Review of Chang Ping’s “Humanistic Criticism of Contemporary Art” - MENG, Keqing (Journal of Research for Christianity in China (JRCC), 2022)
Zha Changping, Humanistic Criticism of Contemporary Art. Nanjing: Jiangsu Phoenix Fine Arts Publishing House, 2019. Includes multiple color illustrations. Price: ¥88.